PENGARUH INSEKTISIDA NABATI DAUN TEMBAKAU DAN PEPAYA TERHADAP MORTALITAS ULAT GRAYAK (Spodoptera litura) - Army Dita Serdani; Jeka Widiatmanta; Angelita Kurnia Ardi (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
Armyworm (Spodoptera litura) is a polyphagous pest that commonly attacks vegetable cultivation. Farmers are currently still using chemical control, namely spraying chemical pesticides. The consequences are environmental problems, resistance and even pest explosions. One way to overcome this is by using tobacco and papaya leaves as vegetable pesticides. Tobacco leaves and papaya leaves can be used as vegetable insecticides because they contain alkaloids, tannins and saponins. The research was conducted in Sukorejo Village starting from May-July 2022. The study used a Randomized Block Design where there were 10 treatments and each treatment was repeated 3 times so there were 30 experimental units. The observed variables were mortality, the percentage of pupae and imago formed, then the data were analyzed using ANOVA and if the results were significantly different a follow-up test was carried out with a 5% BNJ. The results of the ANOVA test showed that the concentration of 40 g papaya leaves + 40 g/l water of tobacco leaves (D8) was the best concentration which caused 87.67% mortality and the lowest percentage of pupa formation was 13.56%.